A recongurable computing system for an autonomous sailboat
This paper presents the computing infrastructure used in an autonomous unmanned smallscale sailboat. The system is build on a reconfigurable FPGA and includes custom designed interfaces for the various sensors and actuators used in the sailboat. The central processing unit is a 32-bit RISC microprocessor (Microblaze from XILINX) implemented as a soft IP (Intellectual Property) core, running at a maximum frequency of 50 MHz. The computing system runs uClinux, a simplified version of the popular Linux operating system. The usage of a reconfigurable platform enables the possibility to reconfigure completely the processing and control hardware system. This facilitates enormously the development of the control system and allows the selection of different hardware control systems, according to the navigation requirements and environmental conditions.